2017
DOI: 10.1021/acs.orglett.7b03418
|View full text |Cite
|
Sign up to set email alerts
|

Focused Genome Mining of Structurally Related Sesterterpenes: Enzymatic Formation of Enantiomeric and Diastereomeric Products

Abstract: Heterologous expression of four clade-A bifunctional terpene synthases (BFTSs), giving di/sesterterpenes with unique polycyclic carbon skeletons such as sesterfisherol, enabled the isolation of the sesterterpenes Bm1, Bm2, Bm3, and Pb1. Their structures suggested that formation of the products occurs via various diastereomeric carbocation intermediates, allowing the proposal that clade-A BFTSs catalyze three-step cyclizations using several stereofacial combinations of allylic cation-olefin pairs in the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 18 publications
0
46
0
8
Order By: Relevance
“…We recently reported sesterfisherol synthase NfSS 3 that is a representative enzyme of fungal sesterterpene synthase and closely related enzymes 4 . Isotopic labeling experiments with [1- 13 C, 2 H 3 ]acetate and (8,8- 2 H 2 ) geranylgeranyl diphosphate indicated that the 13 C-labeling pattern of sesterfisherol ( 1 ) is identical to that of GFPP, and multiple hydrogen shifts take place during the cyclization process.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported sesterfisherol synthase NfSS 3 that is a representative enzyme of fungal sesterterpene synthase and closely related enzymes 4 . Isotopic labeling experiments with [1- 13 C, 2 H 3 ]acetate and (8,8- 2 H 2 ) geranylgeranyl diphosphate indicated that the 13 C-labeling pattern of sesterfisherol ( 1 ) is identical to that of GFPP, and multiple hydrogen shifts take place during the cyclization process.…”
Section: Introductionmentioning
confidence: 99%
“…6B). 45) The structure of Bm2, including its absolute configuration, is the same as that of the tetracyclic carbocation, whereas the other three products are diastereomers of the bicyclic and tricyclic carbocations. This observation suggested that clade I CPF-TSs can generate various enantiomeric and diastereomeric cation intermediates that give rise to a diverse array of structural derivatives.…”
Section: Genome Mining Of Novel Nps From Silent Bgcsmentioning
confidence: 99%
“…A detailed theoretical study of sesterfisherol biosynthesis was published by Sato et al (Narita et al, 2017; Sato et al, 2018b). While they were exploring the cyclization mechanisms of sesterfisherol, a deep minima was found that required extraordinarily high energy, which was different from the activation energy in terpene biosynthesis.…”
Section: Terpenoidsmentioning
confidence: 99%